STRATEGIC CLOUD MIGRATION FRAMEWORK: A COMPREHENSIVE APPROACH TO RESILIENT MULTI-CLOUDARCHITECTURE - KAIMAL, SREEJITH (IPHO-Journal of Advance Research in Science And Engineering, 2025)
Migration to the cloud has moved from infrastructure renewal to strategic programs demanding holistic frameworks for dealing with vendor dependencies, regulatory challenges, and geopolitical risks. This framework proposes systemic methods that integrate workload categorization, vendor-independent architectures, data governance policies, and geopolitical risk management. Workload categorization creates criticality hierarchies and determines system interdependencies and technological constraints. Mitigation of vendor lock-in uses open standards, containerization, and Infrastructure-as-Code that is cross-platform agnostic. Data portability plans utilize AI-powered interoperability supporting smooth multi-cloud operations.Geopolitical risk policies integrate AI-based monitoring and area failover settings, overcoming regulation differences and service outages.Financial assessment indicates active-active deployments calling for double to triple the cost of active-passive arrangements, with cold backup options demanding low recurring expenses. The model offers systematic methods for dealing with sophisticated regulatory environments while preserving operational efficiency and strategic flexibility in modern multi-cloud platforms.